2023
DOI: 10.1111/pce.14557
|View full text |Cite
|
Sign up to set email alerts
|

Combined genome‐wide association study and epistasis analysis reveal multifaceted genetic architectures of plant height in Asian cultivated rice

Abstract: Plant height (PH) in rice (Oryza sativa) is an important trait for its adaptation and agricultural performance. Discovery of the semi-dwarf1 (SD1) mutation initiated the Green Revolution, boosting rice yield and fitness, but the underlying genetic regulation of PH in rice remains largely unknown. Here, we performed genome-wide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Moreover, we performed transient assay in protoplast, and showed that OsWRKY78 can efficiently activate the expression of OsGA20ox‐1, OsGA20ox‐3, OsGA3ox‐1 , but did not regulate the expression of OsGA2ox‐3 and OsGA2ox‐4 (Figures 4D–F, S7). In addition, to investigate how OsWRKY78 indirectly regulates OsGA2ox‐3 and OsGA2ox‐4 , we examined the expression of the published upstream regulator of GA metabolism genes, including OsHOX12, OsMADS56 , and OsMADS57 (Chu et al, 2019; Gao et al, 2016; Hong et al, 2023), and found they show similar expressions between WT and oswrky78 (Figure S8). Finally, to provide the genetic evidence of OsWRKY78 regulating GA biosynthesis, we chose OsGA20ox‐1 as representative and generated OsGA20ox‐1 overexpression plants in both WT and oswrky78 backgrounds (Figure 4G, H).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we performed transient assay in protoplast, and showed that OsWRKY78 can efficiently activate the expression of OsGA20ox‐1, OsGA20ox‐3, OsGA3ox‐1 , but did not regulate the expression of OsGA2ox‐3 and OsGA2ox‐4 (Figures 4D–F, S7). In addition, to investigate how OsWRKY78 indirectly regulates OsGA2ox‐3 and OsGA2ox‐4 , we examined the expression of the published upstream regulator of GA metabolism genes, including OsHOX12, OsMADS56 , and OsMADS57 (Chu et al, 2019; Gao et al, 2016; Hong et al, 2023), and found they show similar expressions between WT and oswrky78 (Figure S8). Finally, to provide the genetic evidence of OsWRKY78 regulating GA biosynthesis, we chose OsGA20ox‐1 as representative and generated OsGA20ox‐1 overexpression plants in both WT and oswrky78 backgrounds (Figure 4G, H).…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of physiological effects of natural variation in seed glycerolipids are still ongoing in this group. Hong, Su, et al (2023) also performed GWAS on plant height in whole 619 populations and in three japonica subpopulations with different SD1 haplotypes after the effect of SD1 is fixed, and revealed multifaceted genetic architectures of plant height in rice, and identified two sets of QTL epistatic interactive networks in the subgroup harboring Nipponbare‐specific SD1 haplotype are found to be multieffective QTL/genes, participating as well in flowering, which links plant height QTL/genes with adaptive events such as flowering in japonica rice (Hong, Su, et al, 2023), reflecting association of plant height trait with different environmental adaptation events particularly in japonica subpopulations.…”
Section: Natural Variations In Rice Resiliencementioning
confidence: 99%
“…The past few years have seen a remarkable acceleration in our understanding of the intricate interplay between complex traits and the molecular mechanisms driving them. Researchers worldwide have delved deeply into the genetic architectures of key annual crops [7,8], unearthing novel insights into yield potential [9,10], stress tolerance [10,11], and nutritional quality [12,13]. Some researchers have constructed various mapping groups to analyze the genetic mechanisms of complex traits, such as F 2 populations [14], RIL populations [15], NAM populations [16], MAGIC populations [17], CUBIC populations [18], etc.…”
Section: Introductionmentioning
confidence: 99%